Кваліметричний підхід до моделювання оцінки синергетичного ефекту функціонування транспортно-логістичної системи - Гриценко, В.І.; Бажан, Л.І. (Control systems & computers, 2021)
Запропоновано непараметричний метод DEA (Data Envelopment Analysis), який є високоінтелектуальним методом аналізу середовища функціонування з огляду на те, що його методологія базується на інтелектуальній технології бенчмаркінгу – порівняльного аналізу на основі еталонних показників (стандартів). Розроблена на основі методу DEA модель дозволяє оцінювати транспортно-логістичну систему як стійку в деякому проміжку часу, використовуючи нормативну якість виконуваних логістичних послуг. Purpose. For the sustainable development of the transport and logistics system, it is necessary to develop a concept for ensuring the assessment of the quality of logistics services based on a qualimetric approach to obtain a synergistic effect of the system’s functioning Results. The transport and logistics system, as an ordered set of elements with the certain connections. It has the special systemic properties that are not inherent in individual elements, but allow for a synergistic effect in the process of functioning. The effect of logistic synergy arises in the process of mutual strengthening of relations between the internal and external environment at the level of input and output material and information flows. Quality management of logistics services is based on the provision of operational information about the quality of logistics services and timely management decisions to ensure this quality. In accordance with the principles of the standards, product quality management is aimed at ensuring customer satisfaction and continuously improving the quality of logistics services.